Maqashid Syariah Sebagai Filsafat Hukum Islam: Studi Pemikiran Jesser Auda - Agus Indra Cahyadi; Ummarullah Missai; Rosdianto; Muannif Ridwan; Agung Setiabudi (Universitas Islam Indragiri, 2024)
The main aim of this research is to dig deeper into Maqasid Syariah as a Philosophy of Islamic Law from the Thought of Jasser Auda. The method used in this research uses the library study method, using various sources of reading material such as books, journals, scientific works and so on. Jasser Auda's thinking attempts to approach Islamic law in various dimensions, which is then called a multi-disciplinary approach. This multi-disciplinary approach includes established methodological aspects formulated by past scholars, such as ushul fiqh, tafsir science, etc. Apart from that, the field approach of philosophy and systems theory is the most significant approach in determining the dynamics of Islamic law. This multidisciplinary approach became known as the maqashid approach formulated by Jasser Auda, namely an approach to fiqh theory that is holistic (kulliyun) and does not limit itself to texts or partial laws. Jassser Auda offers methods in a systems approach as an effort to form a new framework of thinking in understanding Islamic law in the current era. Religious approaches and interpretations are expected to produce legal products that are in accordance with the purposes stated in Islamic law.